Studies on the Bioremediation Potential of Bacteria Isolated from Diesel-contaminated Soils in Kano (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Bioremediation is pollution control technology that uses microorganism to clean up contaminated environment. This study was aimed at assessing the bioremediation potential of bacteria isolated from diesel-contaminated soils and screen them for the ability to remediate diesel contaminated environment using their potential to degrade diesel as carbon and energy source. Diesel-contaminated soil samples were collected using standard method. Bacteria were isolated, characterized   and identified using standard microbiological procedures.  The identified bacteria species were subsequently screened for diesel biodegradation potential in Bushnell Haas Media (BHM). Optimum conditions (pH, temperature, and diesel concentrations) for biodegradation were determined. The results showed that Bacillus subtilis and Bacillus megaterium were the most potent species identified. Bacillus subtilis and Bacillus megaterium were observed to utilize diesel as the sole carbon source in which they degrade 79% and 80% diesel during the 25 days incubation study respectively. Optimum diesel biodegradation for Bacillus subtilis and Bacillus megaterium were temperatures of between 30 and 35 C, pH between 6 and 7, diesel concentrations between 3% and 2%. The findings of this study demonstrated the species' ability to digest fuel, suggesting their potential utility in the broad-scale bioremediation of diesel-contaminated soils.
Keywords: Bacteria; Biodegradation; Bacillus spp.; Contamination; Diesel